Analisis Sidik Jari DNA Plasma Nutfah Kedelai Menggunakan Markah SSR - Santoso, Tri Joko; Utami, Dwinita Wikan; Septiningsih, Endang M. (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
Accuracy is an important issue for plant germplasm identification, especially forvarietal conformation, registration, and plant protection. A study was conducted to determine genetic variation in 96 soybean accessions based on variation in size and number alelles using fluorescently-labeled SSR (Simple Sequence Repeat) markers on a capillary-electrophoresis DNA analyzer. This technology can be used to measure sizes of DNA fragments accurately and the genotyping protocol can be automated in a high-throughput manner. In addition, the germplasm as a whole can be further analyzed to measure the amount of genetic diversity and to identify agronomically-important genes or alleles for variety improvement. Results of the study indicated that nearly all the soyben accessions tested showed unique DNA fingerprints or genetic identities. The rare alleles (frequency <5%) that might have the potential in the variety improvement program had also been detected. Identification of the 96 soybean accessions using 10 SSR markers had detected 116 alleles, ranging between 7-19 alleles per locus, with the value of PIC (Polymorphism Information Content), reflecting the value of frequency and allele variation) 0.703. The tendency for clustering together of the allelles in certain groups of the improved soyben varieties indicating that there were close genetic relationships among them. In addition, molecular differences between two accessions having the same names but with different number of registrations were detected. Furthermore, the presence of two soybean accessions with different names but having the same molecular identity was also identified.